Smilde guide : employee, perspectives on culture, loyality, and profit - Spiegelman, Paul, ....- (Dallas : Brown books publishing group, 2012)
Why is a company with a positive culture such an exception these days? Employee loyalty drives customer satisfaction, which in turn drives profit: this is the key to success for Smile Guide author, Paul Spiegelman, and a philosophy he s coined as the Circle of GrowthTM. If compassionate ethical enterprises become the rule instead of the exception, business would be much better positioned to create more sustainable employment and greater long-term growth this is where Spiegelman s tried-and-true people-centric business model comes in. Building a solid culture program is a long process of hard work, but Smile Guide will provide the tips and tools needed to employ a proven means of generating small impacts that will transform your organization for the better.